Исследование возможности снижения остаточных деформаций в технологической оснастке для закалки валов - Мартыненко, Геннадий Юрьевич; Скрынька, Л. М.; Смирнов, М. М.; Пирогов, А. Д. (НТУ "ХПИ", 2006)
In work the researches by definition of the barring opportunity of residual plastic accumulation deformations in technological equipment have been carried out which are used for shaft, rotors etc hardening. It is shown, that thermotensions are the reason of accumulation of residual deformations. The ways of the level thermotensions decreasing at the expense of application thermo-insulating materials have offered
Keywords: термообработка металлоемких деталей; термоциклирование; закалка стальных деталей; оснастка для термообработки деталей; теплопроводность; термоупругость